Evaluation of the therapeutic potential of resveratrol-loaded nanostructured lipid carriers on autosomal recessive spastic ataxia of Charlevoix-Saguenay patient-derived fibroblasts. (1st November 2021) - Şen, Özlem; Emanet, Melis; Marino, Attilio; Belenli Gümüş, Melike; Bartolucci, Martina; Doccini, Stefano; Catalano, Federico; Genchi, Giada Graziana; Santorelli, Filippo Maria; Petretto, Andrea; Ciofani, Gianni
Graphical abstract: Highlights: Resveratrol-loaded NLCs have been proposed as therapeutic agents in ARSACS. Results demonstrated their antioxidant and anti-inflammatory abilities. Transcriptomics and proteomics confirm their therapeutic potentialities. Abstract: Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is a neurological disease characterized by autosomal recessive mutations in the sacsin gene ( SACS ), that cause in patients progressive cerebellar atrophy, damage of the peripheral nerves, and cognitive impairment. No effective therapies have been proposed for ARSACS, even if some evidences suggest that powerful antioxidant agents can be considered as a therapeutic tool. Resveratrol (Res) is a natural polyphenol compound derived from vegetal sources, the application of which in biomedicine is increasing in the latest years owing to its significant therapeutic effects, in particular in neurodegenerative diseases. In this study, we provide evidences about its potential exploitation in the treatment of ARSACS. Because of the low solubility of Res in physiological media, a nanoplatform based on nanostructured lipid carriers is proposed for its encapsulation and delivery. Resveratrol-loaded nanostructured lipid carriers (Res-NLCs) have been synthetized, characterized, and tested on healthy and ARSACS patient fibroblasts. Nanovectors displayed optimal stability and biocompatibility, and excellent antioxidant and anti-inflammatory activities. A comprehensive investigation at gene (with real-time quantitative RT-PCR) and protein (with proteomics) level demonstrated the therapeutic potential of Res-NLCs, encouraging future investigations on pre-clinical models.